Changes in the Composition of the Milk of Racka Sheep During Lactation - Nagy, László; Komlósi, István (Acta Agraria Debreceniensis, 2005)
We examined the changes in the composition of the milk of 36 Racka sheep during lactation. As milking of Racka sheep is not performed anywhere in the country, the test was restricted to the examination of milk components. However, quantity could not be measured. We analysed the fat, protein, lactose, carbamide and somatic cell count content of the milk from sampling. By means of correlation analysis, milk components were compared to the age of ewes, then the number of lactation days. With the advancing of the lactation and by analysing the milk components, we found differences between the two colour-variants of Racka sheep. Additional trials are required to decide whether the differences between the two colour-variants may be considered as constants, or can be attributable to the relatively small number of samples.